2021
DOI: 10.1177/11206721211059327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the change in total corneal astigmatism and actual change in refractive astigmatism in transepithelial photorefractive keratectomy (tPRK), laser in situ keratomileusis (LASIK) and femtosecond laser assisted laser in situ keratomileusis (FsLASIK)

Abstract: Purpose To compare changes in astigmatism by refraction and total corneal astigmatism after tPRK, LASIK and FsLASIK. Setting Specialty Eye Hospital Svjetlost, Zagreb, Croatia. Design Partially masked, semi-randomized, prospective, case-by-case, interventional, clinical study. Methods Patients with a stable refraction (-0.75DS to −8.00DS, astigmatism ≤1.00DC) underwent tPRK, LASIK or FsLASIK without complication. Astigmatism was measured at both corneal surfaces over the central 3.2 mm zone (approximately using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…It has furthermore been shown that refractive astigmatism, which is a subjective measurement, may not accurately reflect corneal astigmatism, an objective measurement. 34 Further studies should be performed to evaluate how the degree of astigmatism influences the accuracy of corneal power measurements. Finally, our study did not include data from the Pentacam corneal power Equivalent-K Readings (EKR) ∆map.…”
Section: Discussionmentioning
confidence: 99%
“…It has furthermore been shown that refractive astigmatism, which is a subjective measurement, may not accurately reflect corneal astigmatism, an objective measurement. 34 Further studies should be performed to evaluate how the degree of astigmatism influences the accuracy of corneal power measurements. Finally, our study did not include data from the Pentacam corneal power Equivalent-K Readings (EKR) ∆map.…”
Section: Discussionmentioning
confidence: 99%